2021
DOI: 10.1002/adfm.202101892
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Electrostatic and Entropy‐Related Mechanisms for Charge‐Transfer Exciton Dissociation at Doped Organic Heterojunctions

Abstract: The electron donor/acceptor (D/A) heterojunction is the core for photocharge generation and recombination in organic photovoltaics (OPVs). Developing practical methods for the D/A heterojunction modification remains challenging and is rarely discussed in OPV research. Herein, the roles of molecular doping at the D/A heterojunction in the charge-transfer exciton dissociation and detailed energy loss are investigated, and new insights are gained into the functions of doping on the OPV performance. Heterojunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 69 publications
1
40
0
Order By: Relevance
“…Alternatively, molecular doping, which introduces extra holes (p‐doping) or electrons (n‐doping) via electrostatic induction or certain chemical reaction, has the potential to regulate these electronic defects. [ 17–22 ] It has been reported that the PCE values of doped OSCs were 17.1% and 17.4% in binary and ternary BHJ films after n‐doping, and the champion value was refreshed as 17.98% by synergistically doping the active layer and electrode interface. [ 23–25 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, molecular doping, which introduces extra holes (p‐doping) or electrons (n‐doping) via electrostatic induction or certain chemical reaction, has the potential to regulate these electronic defects. [ 17–22 ] It has been reported that the PCE values of doped OSCs were 17.1% and 17.4% in binary and ternary BHJ films after n‐doping, and the champion value was refreshed as 17.98% by synergistically doping the active layer and electrode interface. [ 23–25 ]…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, molecular doping, which introduces extra holes (p-doping) or electrons (n-doping) via electrostatic induction or certain chemical reaction, has the potential to regulate these electronic defects. [17][18][19][20][21][22] It has been reported that the PCE values of doped OSCs were 17.1%The semitransparent and colorful properties of organic solar cells (OSCs) attract intensive academic interests due to their potential application in building integrated photovoltaics, wearable electronics, and so forth. The most straightforward and effective method to tune these optical properties is varying the componential ratio in the blend film.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…43,44,50,51 The heterojunction doping facilitates exciton splitting for two reasons: first, heterojunction doping can enhance the built-in potential in the device, which is good for both free carrier generation and collection; second, heterojunction doping provides more vacancies for charge transfer by increasing the density of states (DOS), thus increasing the generation yield of free carriers via entropy gain. 52 Fascinated by these advantages, we further conducted heterojunction doping in OSC material systems with negligible driving force for exciton splitting. The simultaneous enhancement of shortcircuit current (J SC ) and open-circuit voltage (V OC ) demonstrates its promising application in solving the long-standing J SC -V OC compromise in OSC devices.…”
mentioning
confidence: 99%
“…The simultaneous enhancement of shortcircuit current (J SC ) and open-circuit voltage (V OC ) demonstrates its promising application in solving the long-standing J SC -V OC compromise in OSC devices. 52 Herein, we compare two strategies for tuning the semiconducting properties of organic photovoltaic materials in model PHJ devices to examine whether doping can alleviate the electronic defects induced by the imperfect heterojunction morphology. We fabricated the PHJ devices by floating the polymer poly…”
mentioning
confidence: 99%